A Bibliometric Review of the Field Theory: Current Trends and Future Development - Tri Samnuzulsari (Athena: Journal of Social, Culture and Society, 2025)
This study focuses on the development of Field Theory (FT) literature trends through bibliometric analysis for the previous 20 years. The data analyzed consists of 447 peer-reviewed journal articles from 228 sources retrieved in the Web of Science (WoS) database with Social Science Citation Index (SSCI) indexing, from 2003 to October 2022. An overview of 447 articles was presented by utilizing Biblioshiny and HistCite. To visualize the data, we used VOSviewer software. Bibliometric analysis enabled us to chart the development of the FT literature. and its variants, provide a thorough understanding of the FT field's dynamics (structure), and identify journals, authors, subtopics (themes), and their interconnections and network relationships. The results of this study obtained two significant findings, namely that studies on FT grew rapidly from 2003 to 2022, especially in 2016. In addition, there are seven research clusters where neo-institutionalism and Pierre Bourdieu are the dominant themes.